Asset Pricing with Endogenous Disasters - Tiu, Cristian; Yoeli, Uzi (Review of Financial Studies, 2013)
[We develop a parsimonious model in which frictions in the labor market may turn small, continuous labor productivity declines into large drops in employment, endogenously causing disasters. Assuming one state variable and CRRA agents, we solve for prices in closed form, calibrate the model using labor market data, and show that this simple setting captures the high, countercyclical volatility and equity premium observed in the United States. Moreover, returns in our model are conditionally predicted by dividend yields. Finally, as in the data, in our setting the disasters are larger when the capital's share of income is higher.]